Harry Lineback making Moravian stars, 1959. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 11-22-59 p.C1.
Harry Lineback making Moravian stars, 1959.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth